A two-mechanism and multiscale compatible approach for solid state electrolytes of (Li-ion) batteries. (April 2022) - Cabras, L.; Danilov, D.; Subber, W.; Oancea, V.; Salvadori, A.
Abstract: All-solid-state batteries are claimed to be the next-generation battery system, in view of their safety accompanied by high energy densities. A new advanced, multiscale compatible, and fully three-dimensional model for solid electrolytes is presented in this note. The response of the electrolyte is profoundly studied theoretically and numerically, analyzing the equilibrium and steady-state behaviors, the limiting factors, as well as the most relevant constitutive parameters according to the sensitivity analysis of the model, the novel model is finally validated in accordance with experimental results. Highlights: We developed a novel two-mechanisms model for solid state electrolyte. The model is multiscale compatible and straightforwardly extendible to mechanics. We identified and discussed the two mechanisms at steady state. We identified limiting factors for solid electrolytes, during transients. Constitutive theory and weak forms are framed in a rigorous PDEs setting.